The Application of Wordwall-Based Digital Media Through the Problem-Based Learning Model to Improve Learning Outcomes in the Pancasila Education Course for Third Grade Students - Chaterine Angel Anugrah Natalia; Ribut Prastiwi Sriwijayanti; Didit Yulian Kasdriyanto (International Journal of Educational Evaluation and Policy Analysis, 2026)
The poor levels of student engagement and learning accomplishment among third-grade students at SDN Banjarsawah 2 in Probolinggo in the topic of Pancasila, which were brought on by the employment of dull lecture-based approaches, served as the impetus for this two stage classroom action research (CAR). The minimal accomplishment level (CCC), which is 75, had not yet been attained by many students. The goal of this study was to employ the digital tool Wordwall in the context of problem-based learning (PBL) to enhance student engagement and learning outcomes in the “following rules” curriculum. Fifteen students served as the study's subjects. Tests, documentation, and observation were used to gather data, which were then subjected to quantitative, qualitative, and descriptive analysis. The analysis's findings indicated a notable rise at every level. Just 20% of pupils in the pre-cycle demonstrated mastery of the standard curriculum (3 individuals). Following the intervention, the proportion rose to 60% (9 students) in the first cycle and 86.67% (13 students) in the second. As a result, student learning activities increased from the first cycle's "adequate" category (63.3%) to the second cycle's "very good" category (100%). In conclusion, third-grade elementary school students' engagement and learning outcomes have improved when the Wordwall digital media is used in conjunction with problem-based learning (PBL).